The voyage of the Sea Wolf - Bunting, Eve, 1928- (Sleeping Bear Press, 2012)
After having been marooned on an island for ten days, Catherine and William are finally rescued and brought aboard a pirate ship that is captained by a woman who takes a liking to William and forbids Catherine, his true love, from seeing him.